Method for preparing high-strength and high-toughness PcBN cutter from NbNiCrMnMo reinforced superfine Ti (C, N)

By using NbNiCrMnMo in PcBN tools to enhance ultrafine Ti(C,N)-based materials, forming a core ring structure of (Ti,Nb,Ni,Cr,Mn,Mo)(C,N), the problem of degradation in performance of traditional PcBN tools in high temperature and high pressure environments is solved, and the strength, hardness and toughness of the tool are significantly improved.

CN119703057APending Publication Date: 2025-03-28HENAN UNIVERSITY OF TECHNOLOGY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411921717.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The performance of traditional PcBN tools decreases in high temperature, high pressure and high wear environments, the binding strength of the binding agent and cBN is insufficient, and the toughness of PcBN needs to be improved.

Method used

The ultrafine Ti(C,N)-based material is enhanced by using NbNiCrMnMo to form a core ring structure of (Ti,Nb,Ni,Cr,Mn,Mo)(C,N) under high temperature and high pressure, so as to improve the refinement of ceramic hard phase grains and the dissolution and diffusion precipitation of ceramics and carbides, and enhance the overall performance of PcBN tools.

Benefits of technology

It significantly improves the strength, hardness and toughness of PcBN tools, extends service life, and especially shows excellent performance when processing high-temperature alloys and cemented carbides.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-strength and high-toughness PcBN cutter from NbNiCrMnMo reinforced superfine Ti (C, N), and belongs to the field of manufacturing of superhard materials. The method comprises the following steps: performing acid-alkali pretreatment on cBN powder of 4-6 microns, uniformly mixing the cBN powder with Ti (C, N) powder of 2-4 microns and NbNiCrMnMo powder of 10 microns according to a proper proportion, performing vacuum drying, filling a mold with the mixture to assemble a synthetic block, putting the synthetic block into a cubic press to prepare a PcBN cutter blank at high temperature and high pressure, and performing brazing on the PcBN cutter blank and a WC alloy to prepare the PcBN cutter. The method is simple and controllable in process, easy to operate, high in efficiency, low in cost and capable of meeting large-scale industrial production, the high-strength, high-toughness and high-hardness PcBN cutter can be obtained through a three-section type heating mode high-temperature and high-pressure process, the service life of the PcBN cutter can be remarkably prolonged, and the PcBN cutter particularly shows excellent performance when high-temperature alloy, hard alloy and other difficult-to-machine materials are machined.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention patent belongs to the field of superhard material manufacturing, and in particular relates to a method for preparing high-strength and high-toughness PcBN cutting tools by using NbNiCrMnMo reinforced ultrafine Ti(C,N). Background Art

[0002] In the current manufacturing industry, the performance requirements for tool materials are becoming increasingly stringent, especially in the field of high-speed and high-precision machining. Polycrystalline cubic boron nitride (PcBN), as a superhard material, has been widely used in the field of high-end manufacturing due to its excellent physical and chemical properties. PcBN not only has high hardness, but also has good thermal and chemical stability, making it an ideal choice for machining difficult-to-machine materials. However, when faced with extreme machining conditions, such as high temperature, high pressure and high wear environment, there is still a problem of performance degradation. This is mainly because the bonding strength between the binder and cubic boron nitride (cBN) in traditional PcBN tools is weak, and it cannot provide sufficient support under these conditions, limiting its application range and efficiency. In addition, the toughness of PcBN tools also needs to be improved. In order to solve this problem, people have been seeking various methods to improve the performance of the binder itself, the bonding strength between the binder and cBN, and the toughness of PcBN, so as to improve the overall performance of PcBN tools, broaden their application areas and extend their service life, so as to reduce production costs and improve product efficiency.

[0003] Cermets combine the advantages of metals and ceramics, and have the characteristics of high hardness, high strength, high temperature resistance, corrosion resistance and good toughness. Cermets represented by Ti(C,N)-based cermets have gradually attracted widespread attention as an emerging cutting tool material in recent years. Cermet tools still have good performance under high temperature conditions. In addition, the service life and cutting speed of cermets have improved compared with cemented carbide tools, which are about 2-5 times and 3-10 times that of cemented carbide tools. The most important thing is that the raw material resources of cermets are abundant and the production cost is low. In short, cermets have both the high hardness, high temperature resistance and chemical stability of ceramics and the toughness and thermal conductivity of metals. Therefore, cermets are a new star material for preparing cutting tools with better performance. Its application potential is recognized by more and more people, and it is the most ideal substitute for WC-Co-based cemented carbide cutting tools.

[0004] So far, the large-scale application of Ti(C,N)-based cermets is still limited. The main reason is that Ti(C,N) is not as wettable as WC with the binding phase Ni / Co, which makes its toughness generally inferior to that of cemented carbide systems. So how to develop Ti(C,N)-based cermets with higher strength and toughness has a far-reaching impact on the cutting field and even the industrial field. Around this key issue, there are currently many studies based on material composition design and optimization, preparation process design and optimization, etc. to improve and enhance the performance of Ti(C,N)-based cermets.

[0005] Through exploration in ultrafine Ti(C,N)-based cermets, the researchers found that ultrafine-grained Ti(C,N)-based cermets have better comprehensive properties than other metal ceramics, such as hardness, toughness and wear resistance, which provides a broader development space for its industrial applications.

[0006] High Entropy Alloys (HEAs) have the special properties of high strength, high hardness, high wear resistance, high fracture toughness, excellent low temperature performance and structural stability, good corrosion resistance and oxidation resistance. They are used in a variety of fields such as aerospace, automotive industry, electronics industry, nuclear energy and other military applications, medical equipment, energy conversion and storage. Using high entropy alloys as binders can improve the performance of the binder itself, thereby improving the overall performance of PcBN. Among the many high entropy alloy systems, NbNiCrMnMo series high entropy alloys are the most widely studied high entropy alloys. However, in the prior art, no method has been found to use ultrafine Ti(C,N) and NbNiCrMnMo to prepare high-strength and high-toughness PcBN tools. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing high-strength and high-toughness PcBN tools by NbNiCrMnMo reinforced ultrafine Ti(C,N). By adding NbNiCrMnMo to the Ti(C,N) matrix, (Ti,Nb,Ni,Cr,Mn,Mo)(C,N) can be formed under high temperature and high pressure, so that the core ring structure of the metal ceramic is most evenly distributed, the ceramic hard phase grains are refined, and the ceramic and carbide are dissolved, diffused and precipitated. In the preparation of PcBN tools at high temperature and high pressure, the effect of dispersion strengthening is played, thereby improving the performance and life of the PcBN tools.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] A method for preparing a high-strength and high-toughness PcBN tool by using NbNiCrMnMo reinforced ultrafine Ti(C,N), comprising the following steps:

[0010] S1. Select raw materials, which include the following components by mass percentage: 80%-85% main crystal phase, 13%-19% binder, and 0.5%-3% reinforcing agent; wherein the main crystal phase is cBN powder, the binder is Ti(C,N) powder, and the reinforcing agent is NbNiCrMnMo powder;

[0011] S2, mixing, adding the main crystal phase, binder and reinforcing agent into the solvent in proportion and mixing evenly to obtain a mixed slurry, placing the obtained mixed slurry in a vacuum drying oven for drying and high temperature treatment to obtain a mixed powder;

[0012] S3, sintering, filling the mixed powder into a synthesis mold to form a synthesis block, sintering at high temperature and high pressure in a six-sided top press according to the set process parameters, unloading the pressure and cooling to room temperature to obtain a PCBN sample;

[0013] S4. Brazing the PcBN sample sintered at high temperature and high pressure with the WC alloy substrate to obtain a PcBN tool.

[0014] Preferably, the cBN powder has a grain size of 4 μm-6 μm and a purity of 99.9%.

[0015] Preferably, the Ti(C,N) has a grain size of 2 μm-4 μm and a purity of 99.9%.

[0016] Preferably, the NbNiCrMnMo powder has a grain size of 10 μm and a purity of 99.9%.

[0017] Preferably, in step S1, the cBN powder is first placed in a 10% to 30% dilute hydrochloric acid solution, boiled for 10 min-50 min, and then washed with distilled water, then placed in a 10% to 30% NaOH solution, boiled for 10 min-50 min, and then washed with distilled water, and then after centrifugation, first washed with distilled water, then washed with anhydrous ethanol, and finally vacuum dried for standby use.

[0018] Preferably, in step S2, a ball mill is used for mixing, and in the ball mill, the weight ratio of the solvent, the raw material, and the grinding balls is 2:1:3, the mixing time is 24h to 30h, and the grinding balls are zirconia balls or cemented carbide balls.

[0019] Preferably, in step S2, the solvent is anhydrous ethanol.

[0020] Preferably, in step S2, the drying is carried out at 3.0×10 -3 The samples were dried under vacuum at 60°C for 24 h.

[0021] Preferably, in step S2, the high temperature treatment is performed at 3.0×10-3 Pa in a vacuum environment and treated at a temperature of 500°C-600°C for 1h-3h.

[0022] Preferably, the high temperature and high pressure sintering in step S3 includes the following steps: first increase the pressure to 5.0GPa-6.0GPa and then keep it unchanged, heat it to 600℃ at a heating rate of 100℃ / min and keep it warm for 5min, continue to heat it to 1000℃ at a heating rate of 100℃ / min and keep it warm for 3min, then continue to heat it to 1400℃-1500℃ at a heating rate of 50℃ / min, and keep it warm for 5-10min.

[0023] The present invention also includes other steps that enable it to be used normally, which are all conventional technical means in the field; in addition, the steps not limited in the present invention all adopt conventional means in the field and will not be described in detail here.

[0024] The working principle of the present invention is:

[0025] The present invention uses a metal ceramic Ti (C, N) binder to replace a general metal binder or a ceramic binder, and utilizes the high strength and high toughness of the metal ceramic Ti (C, N) itself to improve the performance of the binder itself, and improve the overall strength and hardness of PcBN. The present invention uses fine grains to improve the strength, hardness and toughness of the material. 2μm-4μm Ti (C, N) powder, 10μm high entropy alloy NbNiCrMnMo powder and 4μm-6μm cBN powder can not only improve the strength of the binder itself and the bonding strength between the binder and cBN, but also improve the toughness of PcBN, so that the overall performance of PcBN is enhanced. The addition of high entropy alloy NbNiCrMnMo powder can refine the grain size of Ti(C,N) powder under high temperature and high pressure, and at the same time form (Ti,Nb,Ni,Cr,Mn,Mo)(C,N), refine the grains of ceramic hard phase, dissolve, diffuse and precipitate ceramics and carbides, and play a role of dispersion strengthening in the preparation of PcBN tools under high temperature and high pressure, thereby improving the overall performance of PcBN. When the above materials are sintered in appropriate proportions and with appropriate high temperature and high pressure processes, the high hardness of cBN itself, the high strength, high fracture toughness and wear resistance of Ti(C,N) binder, the high strength, high hardness, high wear resistance, high fracture toughness, excellent low temperature performance and structural stability, good corrosion resistance and oxidation resistance of high entropy alloy NbNiCrMnMo can be used, and a high-strength, high-toughness and super-hard PcBN tool can be obtained by selecting an appropriate high temperature and high pressure process.

[0026] The beneficial effects of the present invention are:

[0027] The process of the present invention is simple, controllable, easy to operate, efficient, and low in cost, and can meet the needs of large-scale industrial production. It utilizes the high hardness of cBN itself, the high hardness, high strength, and good toughness of Ti(C, N) metal ceramics, and the high strength, high hardness, and high fracture toughness of NbNiCrMnMo. The addition of NbNiCrMnMo powder can refine the grain size of Ti(C, N) powder under high temperature and high pressure, and can form (Ti, Nb, Ni, Cr, Mn, Mo)(C, N), refine the grains of ceramic hard phase, and dissolve, diffuse, and precipitate ceramics and carbides. In the preparation of PcBN tools under high temperature and high pressure, it can play a role of dispersion strengthening and improve the overall performance of PcBN. Optimizing the high temperature and high pressure process in a three-stage heating method can obtain a high-strength, high-toughness, and high-hardness PcBN tool, significantly improving the life of the PcBN tool, especially showing excellent performance when processing difficult-to-process materials such as high-temperature alloys and cemented carbides. DETAILED DESCRIPTION

[0028] The present invention is further described below with specific examples. The illustrative embodiments and descriptions of the present invention are used to explain the present invention, but are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work, any modifications, equivalent substitutions, improvements, etc., should be included in the protection scope of the present invention.

[0029] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0030] The devices used in the present invention are not particularly limited and can be any of the commonly used devices in the art.

[0031] Example 1

[0032] The method for preparing the PcBN tool comprises the following steps:

[0033] A method for preparing a high-strength and high-toughness PcBN tool by using NbNiCrMnMo reinforced ultrafine Ti(C,N), comprising the following steps:

[0034] S1. Select raw materials, which include the following components by mass percentage: 80% main crystal phase, 19% binder, and 1.0% reinforcing agent; wherein the main crystal phase is cBN powder, with a grain size of 4μm-6μm and a purity of 99.9%. The binder is Ti(C,N) powder, with a grain size of 2μm-4μm and a purity of 99.9%. The reinforcing agent is NbNiCrMnMo powder, with a grain size of 10μm and a purity of 99.9%.

[0035] In this embodiment, cBN powder was purchased from Zhengzhou Zhongnan Jet Superhard Materials Co., Ltd., model CBNM-W, Ti(C,N) powder was purchased from Hebei Lebo Metal Materials Technology Co., Ltd., and NbNiCrMnMo powder was purchased from Beijing New Materials Research Institute.

[0036] S2, mixing, adding the main crystal phase, binder and reinforcing agent into the solvent in proportion and mixing evenly to obtain a mixed slurry, placing the obtained mixed slurry in a vacuum drying oven for drying and high temperature treatment to obtain a mixed powder;

[0037] S3, sintering, filling the mixed powder into a synthesis mold to form a synthesis block, sintering at high temperature and high pressure in a six-sided top press according to the set process parameters, unloading the pressure and cooling to room temperature to obtain a PCBN sample;

[0038] S4. Brazing the PcBN sample sintered at high temperature and high pressure with the WC alloy substrate to obtain a PcBN tool.

[0039] In step S1, the cBN powder is first placed in a 30% dilute hydrochloric acid solution, boiled for 30 minutes, and then washed with distilled water. It is then placed in a 30% NaOH solution, boiled for 30 minutes and washed with distilled water. After centrifugation, it is first washed with distilled water, then washed with anhydrous ethanol, and finally vacuum dried for use.

[0040] In step S2, a high-energy ball mill is used for mixing, the speed is 300 r / min, the mixing time is 24 h, and the weight ratio of the solvent, raw material, and grinding ball in the high-energy ball mill is 2:1:3, and the grinding ball is a zirconia ball. The solvent is anhydrous ethanol. The drying is carried out at 3.0×10 -3 Pa vacuum and 60°C vacuum drying for 24 h. -3 Pa in a vacuum environment and treated at 500°C for 1 h.

[0041] In step S3, the high temperature and high pressure sintering includes the following steps: first increase the pressure to 5.0 GPa and then keep it unchanged, heat it to 600°C at a heating rate of 100°C / min and keep it for 5 minutes, continue to heat it to 1000°C at a heating rate of 100°C / min and keep it for 3 minutes, and then continue to heat it to 1400°C at a heating rate of 50°C / min, and keep it for 10 minutes. After the sintering is completed, cool down and release the pressure to take out the sample, and grind and polish the surface of the sample.

[0042] The PcBN samples prepared in Example 1 were subjected to performance tests. The test process used the FM-ARS900 semi-automatic microscopic measurement system of Japan's Future-Tech Company. The microhardness of the sample was measured at a pressure of 30N for 15s, and the fracture toughness was calculated based on the crack size; the flexural strength of the sample was measured using a WDW-50 universal electronic material testing machine. Specific test results: The flexural strength, microhardness and fracture toughness of PcBN were 595MPa, 39.13GPa and 6.85MPa·m respectively. 1 / 2 .

[0043] Example 2

[0044] The only difference between this embodiment and embodiment 1 is that in step S1, the raw materials include the following components in mass percentage: 85% main crystal phase, 13% binder, and 2.0% reinforcing agent; in step S2, during mixing, cemented carbide balls are used as grinding balls, and the mixing time is 30 hours.

[0045] The performance test of the PcBN sample prepared in Example 2 was carried out according to the same test method as in Example 1. The specific test results are as follows: the flexural strength, microhardness and fracture toughness of PcBN are 578 MPa, 42.31 GPa and 6.63 MPa·m 1 / 2 .

[0046] Example 3

[0047] The difference between this embodiment and embodiment 1 is that in step S1, the raw materials include the following components by mass percentage: 80% main crystal phase, 17% binder, and 3.0% reinforcing agent; in step S2, when mixing the materials, cemented carbide balls are used as grinding balls.

[0048] The performance test of the PcBN sample prepared in Example 3 was carried out according to the same test method as in Example 1. The specific test results are as follows: the bending strength, microhardness and fracture toughness values ​​of PcBN are 616MPa, 40.96GPa and 7.33MPa·m 1 / 2 .

[0049] Example 4

[0050] The difference between this embodiment and embodiment 1 is that in step S1, the raw material includes the following components by mass percentage: 83.5% main crystal phase, 16% binder, and 0.5% reinforcing agent.

[0051] The performance test of the PcBN sample prepared in Example 4 was carried out according to the same test method as in Example 1. The specific test results are as follows: the bending strength, microhardness and fracture toughness values ​​of PcBN are 606Pa, 41.28GPa and 6.23MPa·m1 / 2 .

[0052] Example 5

[0053] The difference between this embodiment and embodiment 1 is that in step S2, the high temperature treatment is carried out at 3.0×10 -3 Pa in a vacuum environment and treated at 500°C for 3h.

[0054] The performance test of the PcBN sample prepared in Example 5 was carried out according to the same test method as in Example 1. The specific test results are as follows: the bending strength, microhardness and fracture toughness of PcBN are 601 MPa, 41.18 GPa and 7.36 MPa·m 1 / 2 .

[0055] Example 6

[0056] The difference between this embodiment and embodiment 1 is that in step S2, the high temperature treatment is carried out at 3.0×10 -3 Pa in a vacuum environment and treated at 550°C for 2h.

[0057] The performance test of the PcBN sample prepared in Example 6 was carried out according to the same test method as in Example 1. The specific test results are as follows: the bending strength, microhardness and fracture toughness of PcBN are 611 MPa, 40.37 GPa and 7.26 MPa·m 1 / 2 .

[0058] Example 7

[0059] The difference between this embodiment and embodiment 1 is that in step S2, the high temperature treatment is carried out at 3.0×10 -3 Pa in a vacuum environment and treated at 600°C for 1 h.

[0060] The performance test of the PcBN sample prepared in Example 7 was carried out according to the same test method as in Example 1. The specific test results are as follows: the bending strength, microhardness and fracture toughness values ​​of PcBN are 613MPa, 41.53GPa and 7.08MPa·m 1 / 2 .

[0061] Example 8

[0062] The difference between this embodiment and embodiment 1 is that in step S3, the pressure is first increased to 5.5 GPa and then kept unchanged, the temperature is raised to 600°C at a heating rate of 100°C / min and kept at that temperature for 5 minutes, the temperature is further raised to 1000°C at a heating rate of 100°C / min and kept at that temperature for 3 minutes, and then the temperature is further raised to 1450°C at a heating rate of 50°C / min and kept at that temperature for 10 minutes. After sintering, the sample is cooled and depressurized and taken out, and the surface of the sample is ground and polished.

[0063] The performance test of the PcBN sample prepared in Example 8 was carried out according to the same test method as in Example 1. The specific test results are as follows: the bending strength, microhardness and fracture toughness values ​​of PcBN are 617 MPa, 41.39 GPa and 7.36 MPa·m 1 / 2 .

[0064] Example 9

[0065] The difference between this embodiment and embodiment 1 is that in step S3, the pressure is first increased to 6.0 GPa and then kept unchanged, the temperature is raised to 600°C at a heating rate of 100°C / min and kept at that temperature for 5 minutes, the temperature is further raised to 1000°C at a heating rate of 100°C / min and kept at that temperature for 3 minutes, and then the temperature is further raised to 1500°C at a heating rate of 50°C / min and kept at that temperature for 5 minutes. After the sintering is completed, the temperature is lowered and the pressure is released to take out the sample, and the surface of the sample is ground and polished.

[0066] The performance test of the PcBN sample prepared in Example 9 was carried out according to the same test method as in Example 1. The specific test results are as follows: the bending strength, microhardness and fracture toughness of PcBN are 625MPa, 41.46GPa and 7.45MPa·m 1 / 2 .

[0067] Comparative Example

[0068] This comparative example provides a method for preparing high-strength and high-toughness PcBN cutting tools with ultrafine Ti(C,N), which differs from Example 1 only in that in step S1, the raw material includes the following components by mass percentage: 85% cBN, 15% Ti(C,N).

[0069] The performance test of the PcBN sample prepared in the comparative example was carried out according to the same test method as in Example 1. The specific test results are as follows: the bending strength, microhardness and fracture toughness values ​​of PcBN are 566MPa, 37.91GPa and 6.32MPa·m 1 / 2 .

[0070] It can be seen from the results of Examples 1 to 9 and the comparative examples that due to the high strength, high hardness and high fracture toughness of NbNiCrMnMo itself, and the addition of NbNiCrMnMo powder can make the Ti(C,N) powder grain size more refined and form (Ti,Nb,Ni,Cr,Mn,Mo)(C,N) under high temperature and high pressure, the ceramic hard phase grains are refined, and the ceramic and carbide are dissolved, diffused and precipitated, which can play a role of dispersion strengthening and improve the overall performance of PcBN. Compared with the comparative example, the bending strength, microhardness and fracture toughness values ​​in the examples are increased by 5.12%, 3.22% and 8.39% respectively.

[0071] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A method for preparing high-strength and high-toughness PcBN cutting tools by using NbNiCrMnMo reinforced ultrafine Ti(C,N), characterized in that: The following steps are involved: S1. Select raw materials, which include the following components by mass percentage: 80%-85% main crystal phase, 13%-19% binder, and 0.5%-3% reinforcing agent; wherein the main crystal phase is cBN powder, the binder is Ti(C,N) powder, and the reinforcing agent is NbNiCrMnMo powder; S2, mixing, adding the main crystal phase, binder and reinforcing agent into the solvent in proportion and mixing evenly to obtain a mixed slurry, placing the obtained mixed slurry in a vacuum drying oven for drying and high temperature treatment to obtain a mixed powder; S3, sintering, filling the mixed powder into a synthesis mold to form a synthesis block, sintering at high temperature and high pressure in a six-sided top press according to the set process parameters, unloading the pressure and cooling to room temperature to obtain a PCBN sample; S4. Brazing the PcBN sample sintered at high temperature and high pressure with the WC alloy substrate to obtain a PcBN tool.

2. The method for preparing high-strength and high-toughness PcBN cutting tools by using NbNiCrMnMo reinforced ultrafine Ti(C,N) according to claim 1, characterized in that: The grain size of the cBN powder is 4 μm-6 μm, and the purity is 99.9%.

3. The method for preparing high-strength and high-toughness PcBN cutting tools by using NbNiCrMnMo reinforced ultrafine Ti(C,N) according to claim 2, characterized in that: The Ti(C,N) powder has a grain size of 2 μm-4 μm and a purity of 99.9%.

4. The method for preparing high-strength and high-toughness PcBN cutting tools by using NbNiCrMnMo reinforced ultrafine Ti(C,N) according to claim 3, characterized in that: The grain size of the NbNiCrMnMo powder is 10 μm and the purity is 99.9%.

5. The method for preparing high-strength and high-toughness PcBN cutting tools by using NbNiCrMnMo reinforced ultrafine Ti(C,N) according to claim 4, characterized in that: In step S1, the cBN powder is first placed in a 10% to 30% dilute hydrochloric acid solution, boiled for 10 min-50 min, and then washed with distilled water. It is then placed in a 10% to 30% NaOH solution, boiled for 10 min-50 min, and then washed with distilled water. After centrifugation, it is first washed with distilled water, then washed with anhydrous ethanol, and finally vacuum dried for use.

6. The method for preparing high-strength and high-toughness PcBN cutting tools by using NbNiCrMnMo reinforced ultrafine Ti(C,N) according to claim 1, characterized in that: In step S2, a ball mill is used for mixing, and the weight ratio of the solvent, the raw material, and the grinding balls in the ball mill is 2:1:3, and the mixing time is 24h to 30h. The grinding balls are zirconia balls or cemented carbide balls.

7. The method for preparing high-strength and high-toughness PcBN cutting tools by using NbNiCrMnMo reinforced ultrafine Ti(C,N) according to claim 6, characterized in that: In step S2, the solvent is anhydrous ethanol.

8. The method for preparing high-strength and high-toughness PcBN cutting tools by using NbNiCrMnMo reinforced ultrafine Ti(C,N) according to claim 6, characterized in that: In step S2, the drying is carried out at 3.0×10 -3 The samples were dried under vacuum at 60°C for 24 h.

9. The method for preparing high-strength and high-toughness PcBN cutting tools by using NbNiCrMnMo reinforced ultrafine Ti(C,N) according to claim 6, characterized in that: In step S2, the high temperature treatment is performed at 3.0×10 -3 Pa in a vacuum environment and treated at a temperature of 500°C-600°C for 1h-3h.

10. A method for preparing high-strength and high-toughness PcBN cutting tools by using NbNiCrMnMo reinforced ultrafine Ti(C,N) according to any one of claims 1 to 9, characterized in that: In step S3, the high temperature and high pressure sintering includes the following steps: first increase the pressure to 5.0GPa-6.0GPa and then keep it unchanged, heat it to 600℃ at a heating rate of 100℃ / min and keep it warm for 5min, continue to heat it to 1000℃ at a heating rate of 100℃ / min and keep it warm for 3min, then continue to heat it to 1400℃-1500℃ at a heating rate of 50℃ / min, and the holding time is 5min-10min.